(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
This study deals with interactive e-books because it is one of the technology of the event, which has had its effects on information sources in general, and the aim of the study is the project of converting university books into interactive e-books at the University of Damascus. The study presented in the practical section a proposed project for converting university books into interactive electronic books at the University of Damascus, and indicated the project’s objectives, stages, returns and obstacles to its application. The University of Damascus is not the "Archives and Documents Course", and the study concluded that working on converting university books at the University of Damascus into interactive electronic books is an urgent necessity to impose the nature of the current era with its modern techniques, and that the university book is the first source of information and the main reference for university students, and recommended The study that the implementation of the interactive electronic university books project should be the first step towards transforming education in public universities And special education to interactive based on simulation and interaction with information. The study used the descriptive analytical approach as the appropriate approach to the subject of the study, by describing and analyzing the interactive e-book application project and providing an applied example of that.